FITRAH DAN PENDIDIKAN ISLAM PADA ANAK USIA DINI - Novita Harini; Mahyuddin Barni; Ali Muammar ZA (CV. ADIBA AISHA AMIRA, 2025)
This article discusses the relationship between fitrah and Islamic education in early childhood, emphasizing the importance of understanding and developing children's innate potential as a foundation for optimal growth. Fitrah, which encompasses aspects of faith, intellect, talent, sexuality, aesthetics, individuality, sociality, and physicality, represents an integral component that must be considered in children's education. By referencing the thoughts of Islamic scholars and recent research, this article explains that fitrah-based education focuses on creating an environment that supports the development of all aspects of a child's fitrah. The proposed educational methods include experiential learning in nature, instilling religious values through exemplary behavior, and providing children with space for self-expression. Activities designed must consider the developmental phases of children and avoid placing pressure on them to achieve outcomes that are not aligned with their developmental stages. Emphasizing a holistic approach to education is expected to produce individuals who are not only knowledgeable but also possess good character and can positively contribute to society. Through a profound understanding of fitrah and the application of appropriate educational practices, it is hoped that children can optimally develop their potential, build a strong identity, and become well-rounded individuals with noble morals. This article concludes that the integration of the concept of fitrah within Islamic education is a crucial step in shaping a quality generation that aligns with religious values.